2018
DOI: 10.3389/fphys.2018.00265
|View full text |Cite
|
Sign up to set email alerts
|

Specific Changes in Young Soccer Player's Fitness After Traditional Bilateral vs. Unilateral Combined Strength and Plyometric Training

Abstract: The aim of this study was to compare changes in young soccer player's fitness after traditional bilateral vs. unilateral combined plyometric and strength training. Male athletes were randomly divided in two groups; both received the same training, including strength training for knee extensors and flexors, in addition to horizontal plyometric training drills. The only difference between groups was the mode of drills technique: unilateral (UG; n = 9; age, 17.3 ± 1.1 years) vs. bilateral (TG; n = 9; age, 17.6 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 55 publications
(97 reference statements)
1
36
1
9
Order By: Relevance
“…Additionally, as is done in youth soccer, unilateral drills should be implemented in the training process of young athletes to maximize (neuronal) adaptations. 53 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as is done in youth soccer, unilateral drills should be implemented in the training process of young athletes to maximize (neuronal) adaptations. 53 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, inter-limb asymmetries might also play a role in performance (e.g., greater symmetrical team-sports players seem to be faster that their asymmetrical counterparts) 18,19 . In this regard, strength training is amongst the most frequently used strategies to improve soccer performance and high-intensity actions, as well as to decrease asymmetries 12,14,[20][21][22] .…”
Section: Different Training Methods To Improve Soccer Specific Variabmentioning
confidence: 99%
“…Therefore, training programs should focus on combined bilateral and unilateral strength training to decrease inter-limb asymmetries and to increase performance during F o r P e e r R e v i e w 4 competition. However, relatively few studies have addressed this issue in young soccer players 22,23 . In addition, to the authors´ knowledge, no studies have analyzed the effect of an intervention on inter-limb asymmetry in youth female soccer players, hence, more studies for this population are warranted.…”
Section: Different Training Methods To Improve Soccer Specific Variabmentioning
confidence: 99%
“…The relationship between UL strength training and COD in soccer has been largely investigated [40][41][42][43]. Recently, Núnez et al [39] demonstrated that UL strength training seems to be more effective in improving COD abilities performance than the BL modalities.…”
Section: Introductionmentioning
confidence: 99%